2017
DOI: 10.1101/108704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An oscillopathic approach to developmental dyslexia: from genes to speech processing

Abstract: Developmental dyslexia is a heterogeneous condition entailing problems with reading and spelling. Several genes have been linked or associated to the disease, many of which contribute to the development and function of brain areas that are important for auditory and phonological processing. Nonetheless, a clear link between genes, the brain, and the symptoms of dyslexia is still pending. The goal of this paper is contributing to bridge this gap. With this aim, we have focused on how the dyslexic brain fails to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 232 publications
0
1
0
Order By: Relevance
“…In a series of related papers (Benítez-Burraco and Murphy 2016; Murphy and Benítez-Burraco 2016;Jiménez-Bravo et al, 2017;Benítez-Burraco, 2018a, Wilkinson andMurphy, 2016) we have shown that the distinctive language deficits found in clinical conditions like ASD, SZ, and DD can be satisfactorily construed in terms of an abnormal, disorder-specific pattern of brain rhythmicity. Interestingly, we have also shown that selected candidate genes for the language oscillogenome exhibit a distinctive, disorder-specific pattern of up-and downregulation in the brain of patients.…”
Section: Brain Oscillations and Language Disordersmentioning
confidence: 97%
“…In a series of related papers (Benítez-Burraco and Murphy 2016; Murphy and Benítez-Burraco 2016;Jiménez-Bravo et al, 2017;Benítez-Burraco, 2018a, Wilkinson andMurphy, 2016) we have shown that the distinctive language deficits found in clinical conditions like ASD, SZ, and DD can be satisfactorily construed in terms of an abnormal, disorder-specific pattern of brain rhythmicity. Interestingly, we have also shown that selected candidate genes for the language oscillogenome exhibit a distinctive, disorder-specific pattern of up-and downregulation in the brain of patients.…”
Section: Brain Oscillations and Language Disordersmentioning
confidence: 97%